Anmeldelser - Johnsson, Bengt (Danish Yearbook of Musicology, 1994)
Review of: Rued Langgaard: The Complete Symphonies, Vol. 1-7, Artur Rubinstein Philharmonic Orchestra, dir. Ilya Stupel, Danacord DACOCD 404-410.